2005
DOI: 10.1021/ie049447x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Bubble Column Reactors:  Progress and Limitations

Abstract: Bubble columns are widely used for carrying out gas−liquid and gas−liquid−solid reactions in a variety of industrial applications. The dispersion and interfacial heat- and mass-transfer fluxes, which often limit the overall chemical reaction rates, are closely related to the fluid dynamics of the system through the liquid−gas contact area and the turbulence properties of the flow. There is thus considerable interest, within both academia and industry, to improve the limited understanding of the complex multiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
185
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(192 citation statements)
references
References 127 publications
0
185
0
7
Order By: Relevance
“…Multi-fluid methods have also been employed in the context of bubble flows by Jakobsen, Svendsen, et al [91], [102] and Dorao et al [52] -see the recent review by Jakobsen et al [103] -as well as chemical reactors such as fluidised beds [100]. The multi-fluid approach is fully consistent with population balance formulations for inertial particles (such as the Williams equation), apart from the fact that the latter allows for particles of the same size, at the same position and time instance, to have a distribution of velocities.…”
Section: Population Dynamics Of Inertial Particlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Multi-fluid methods have also been employed in the context of bubble flows by Jakobsen, Svendsen, et al [91], [102] and Dorao et al [52] -see the recent review by Jakobsen et al [103] -as well as chemical reactors such as fluidised beds [100]. The multi-fluid approach is fully consistent with population balance formulations for inertial particles (such as the Williams equation), apart from the fact that the latter allows for particles of the same size, at the same position and time instance, to have a distribution of velocities.…”
Section: Population Dynamics Of Inertial Particlesmentioning
confidence: 99%
“…The multifluid model seems to be the way forward for a population balance formalism of turbulent flows with inertial particles, but its formulation and basic assumptions are still under development even for laminar flows. Progress in that direction has been made in the field of bubble flows, and the reader is referred to the review of Jakobsen et al [103] for that purpose. Finally, a number of works such as Archambault et al [8], [9] and Beck and Watkins [18], [20], [19] have attempted to describe sprays using a small number of low-order moments, an approach that can be considered to lie between the two-fluid and multi-fluid approaches.…”
Section: The Closure Problem For Dispersionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and his co-workers [6] studied the effect of different breakage and coalescence closures and they showed that incompatible kernels produce poor results. Certain experimental and theoretical models for breakage and coalescence kernels are regarded as milestones for the evolution of population balances in the framework of liquid/gas-liquid dispersed phase systems and the evolution of these models is presented in detail by [15].…”
Section: Introductionmentioning
confidence: 99%